Visual Culture In The New Communication Environment: E-Government As A Case Study - Erdal, Cengiz (The Turkish Online Journal of Design Art and Communication, 2012)
Emerging of internet and broadband connection enabling large amount of information to be transferred from one point to another have caused many services to be transferred to virtual environment causing face to face communication is being replaced by screen to screen communication. Consequently, individuals encounter more and more visuals than ever before, which develops and forms the visual culture through new ICT tools. One of the conspicuous applications that shapes visual culture is e-government system requiring effective HCI applications to be put into practice in adapting users to get used to visual interactions changing their deeply rooted transaction habits. This study aims to reveal evolving nature of visual culture in virtual environment as a result of new information communication technology devices serving us as intermediaries between traditional services that we are used to get through face to face communication and their virtual applications in cyberspace. Egovernment system is examined as a case study as it is an outstanding example of visual culture forming tool.
Keywords: ICT; Culture; e-Government; Visual; Kültür; e-devlet; Görsel